The Limited Effects of Estradiol Administration Immediately after Spinal Cord Injury - García-Sánchez, Lyanne M.; Colón-Mercado, Jennifer M.; Torrado-Tapias, Aranza I.; Padín-Díaz, Kenneth; Miranda, Jorge D.; Santiago-Santana, José M. (Puerto Rico Health Sciences Journal, 2023)
Objective: We aimed to investigate estradiol (E2) as a therapeutic drug for spinal cord injury (SCI) and elucidate the disagreement in the field about the use of this hormone after an injury. Methods: Eleven animals underwent surgery (laminectomy at the T9–T10 levels) followed by an intravenous injection (100 μg) of an E2 bolus and the implantation of 0.5cm of Silastic tubing containing 3 mg of E2 (sham E2 + E2 bolus) immediately after the laminectomy. The SCI control animals received a moderate contusion using the Multicenter Animal SCI Study impactor device over the exposed spinal cord followed by an intravenous bolus injection of sesame oil and were implanted with empty Silastic tubing (injury SE + vehicle); treated rats received a bolus of E2 and a Silastic implant with 3 mg of E2 (injury E2 + E2 bolus). Functional locomotor recovery and fine motor coordination were assessed by the Basso, Beattie, and Bresnahan (BBB) open field test and grid-walking tests, respectively, from the acute (7 days post-injury [DPI]) to the chronic stages (35 DPI). Anatomical studies of the cord were performed using Luxol fast blue staining followed by densitometric analysis. Results: As observed in the BBB open field and the grid-walking tests, E2 post-SCI did not improve locomotor function but instead increased spared white matter tissue, in the rostral region. Conclusion: Estradiol post-SCI, at the dose and route of administration used in this study, failed to promote locomotor recovery but partially restored spared white matter tissue.